2021
DOI: 10.1007/s00787-021-01790-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the lives and mental health of Australian adolescents

Abstract: There has been significant disruption to the lives and mental health of adolescents during the COVID-19 pandemic. The purpose of this study was to assess the psychological and lifestyle impact of the pandemic on Australian adolescents, using an online survey, administered during the outbreak. Self-report surveys were administered online to a sample of 760 Australian adolescents aged 12–18 years assessing impact on a range of domains including behaviour, education, relationships, lifestyle factors (exercise, te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
171
3
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(236 citation statements)
references
References 54 publications
(88 reference statements)
27
171
3
11
Order By: Relevance
“…The COVID-19 pandemic has created unprecedented situations by which strict community lockdowns have negatively affected the movement and health behavior in children [11]. Negative consequences like increasing obesity [12,13], pain [14], depression, anxiety, feelings of loneliness [15][16][17], and sleep disturbances [18,19] are closely related to PA levels [31,43,44]. Our findings are similar to others [28,30,45] demonstrating a significant decline in PA in children during COVID compared to pre-COVID.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The COVID-19 pandemic has created unprecedented situations by which strict community lockdowns have negatively affected the movement and health behavior in children [11]. Negative consequences like increasing obesity [12,13], pain [14], depression, anxiety, feelings of loneliness [15][16][17], and sleep disturbances [18,19] are closely related to PA levels [31,43,44]. Our findings are similar to others [28,30,45] demonstrating a significant decline in PA in children during COVID compared to pre-COVID.…”
Section: Discussionsupporting
confidence: 81%
“…Governments implemented restrictions involving school and sport grounds closures resulted in health risks behaviors especially reduced PA and increase SB [11]. The regulations had negative effect on various mental and health aspects in children and youth such as increasing obesity [12,13], pain [14], depression, anxiety, loneliness feelings [15][16][17], sleep disturbances [18,19], decreased cardiorespiratory fitness [20] and many others, affecting especially socio-economic deprived children [11].…”
Section: Introductionmentioning
confidence: 99%
“…We need to acknowledge that obtaining pre-pandemic retrospective estimates of mental health from parents without the use of validated symptoms measures is a limitation of the current research. Further, while our pattern of findings is consistent with other studies that have examined adolescent self-reported symptoms (Magson et al, 2020, Li et al, 2021, we also consider the possibility that parents may not be fully aware of the extent of their child's symptoms, particularly emotional, anxiety or depressive symptoms (Salbach-Andrae et al, 2009) and thus, our results may be an underestimate of these difficulties. Nevertheless, our MENTAL HEALTH OF AUSTRALIAN YOUTH DURING COVID-19 17 results support other research that youth mental health symptoms have deteriorated over the course of the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, younger children would have been more reliant on their parents for educational support and other provision of needs throughout the day. This result is consistent with findings from the UK that preadolescent children tended to experience greater deterioration in mental health symptoms, including emotional symptoms, whereas adolescents' emotional symptoms improved over the first month of lockdown (Waite et al, 2021), perhaps due to an ability to better maintain peer relationships via the use of technology (Li et al, 2021). Longitudinal research investigating the influence of age effects, family stress and peer relationships on changes in mental health symptoms during the course of the pandemic is an important area for future research.…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted to examine adolescents’ sleep during the COVID-19 pandemic have found that, among typically developing adolescents, sleep schedules were delayed [ 32 34 ], sleep duration was extended, and daytime sleepiness decreased [ 34 36 ]. Results regarding the prevalence or severity of sleep disruptions have been inconsistent, with some studies reporting that disruptions worsened [ 32 , 37 39 ] while others found that they improved [ 40 ].…”
Section: Introductionmentioning
confidence: 99%